Expectations and tensions moments in the thesis tutoring in the Faculty of Education at the Pontifical Catholic University of Peru - D. Revilla (Universitat Politècnica de València, 2017)
Universities determine degree methods in order to provide options to students to obtain bachelor's degree in a short term. In the Faculty of Education at the Pontifical Catholic University of Peru (PUCP) there are three ways, one of them, which is the thesis. In this article, we describe the results of a qualitative descriptive study oriented to recognize the expectations on the process of thesis and tensions experienced during the tutoring thesis by graduates of the careers of initial and primary education. We applied a focus group and interviewed a group of graduates of the Faculty of Education licensed in the period 2011- 2013. We also analyzed three documents of the faculty, curriculum, faculty handbook and graduate procedures guide. Graduates interviewed recognize that the development of the thesis is difficult, a task that generates tension and in that process, it is requires a counselor who has time, who owns qualities for interactive communication, who possess knowledge of the subject and research methodology. When the counselor does not meet these aspects, it creates tension in counseling. Other tensions are generated because they lacked practical knowledge about research and have few skills to develop it. Expectations focus on the selection of the counselor, research orientation and institutional cooperating conditions in optimal process thesis counseling. This research contributes to the line of research training and had the support of the University.